Antiferromagnetic Stabilization in the Ti8O12 Cluster. (15th December 2015) - Yu, Xiaohu; Oganov, Artem R.; Popov, Ivan A.; Qian, Guangrui; Boldyrev, Alexander I.
Abstract: Using the evolutionary algorithm USPEX and DFT+U calculations, we predicted a high‐symmetry geometric structure of the bare Ti8 O12 cluster composed of 8 Ti atoms forming a cube, in which O atoms are at midpoints of all of its edges, in excellent agreement with experimental results. Using natural bond orbital analysis, adaptive natural density partitioning algorithm, electron localization function, and partial charge plots, we find the origin of the particular stability of bare Ti8 O12 cluster: unique chemical bonding where eight electrons of Ti atoms interacting with each other in antiferromagnetic fashion to lower the total energy of the system. The bare Ti8 O12 is thus an unusual molecule stabilized by d‐orbital antiferromagnetic coupling.